2009
DOI: 10.3233/jad-2009-1151
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining Alzheimer's Disease: Evidence for a Protective Role for Amyloid-β Protein Precursor and Amyloid-β

Abstract: Alzheimer's disease (AD) is an age-related neurodegenerative disease characterized clinically by cognitive decline and pathologically by the accumulation of amyloid-β-containing senile plaques and neurofibrillary tangles. A great deal of attention has focused on amyloid-β as the major pathogenic mechanisms with the ultimate goal of using amyloid-β lowering therapies as an avenue of treatment. Unfortunately, nearly a quarter century later, no tangible progress has been offered, whereas spectacular failure tends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 39 publications
(37 reference statements)
3
88
0
1
Order By: Relevance
“…46 These findings are in accordance with results from several transgenic mouse lines that express human versions of AD-inducing mutated genes, which show no evidence of strong neuroinflammatory responses nor widespread progressive neuronal cell death. 49 Of further interest, Aβ 1-42 levels in the brains of high-pathology controls were much higher than those in the brains of aged-matched patients with AD, 50 in agreement with a controversial proposal that Aβ 1-42 may be protective rather than toxic, 51 as further discussed below. In addition, PET imaging studies revealed that cognitive status in patients with AD is inversely correlated with microglial activation, but not Aβ load.…”
Section: Inflammation-a Key Playersupporting
confidence: 53%
See 1 more Smart Citation
“…46 These findings are in accordance with results from several transgenic mouse lines that express human versions of AD-inducing mutated genes, which show no evidence of strong neuroinflammatory responses nor widespread progressive neuronal cell death. 49 Of further interest, Aβ 1-42 levels in the brains of high-pathology controls were much higher than those in the brains of aged-matched patients with AD, 50 in agreement with a controversial proposal that Aβ 1-42 may be protective rather than toxic, 51 as further discussed below. In addition, PET imaging studies revealed that cognitive status in patients with AD is inversely correlated with microglial activation, but not Aβ load.…”
Section: Inflammation-a Key Playersupporting
confidence: 53%
“…In addition, physiologically produced Aβ 1-42 peptide may not represent the neurotoxic Aβ species, but an acute-phase reactant that is triggered by ongoing neurodegenerative processes, as suggested previously. 51 Although axonal degeneration precedes and may precipitate plaque formation, pronounced cell death and progressive neurodegeneration are late features in AD. Therefore, certain transport processes might remain active at early stages of the disease, despite the overt axonopathy and amyloid plaque deposition.…”
Section: From Varicosities To Degenerationmentioning
confidence: 99%
“…There is currently preference for the latter model since disease progression is correlated with the formation of soluble protofibrils rather than the burden of the amyloid plaques. [46][47][48][49] Misfolded proteins are normally sequestered or neutralized by cellular defense mechanisms which include the chaperone, proteasome and/or autophagosome responses. Thus one pathogenic possibility is that these responses are affected during AD such that normal protein turnover, which is essential for cell survival, cannot function.…”
Section: -15mentioning
confidence: 99%
“…More recently, new evidence has suggested that oligomeric Ab, rather than extracellular fibrillary Ab, may be the most toxic entity [4,5]. Nevertheless, the poor correlation between Ab deposits and SAD has prompted a re-examination of the etiological significance of Ab, since Ab-lowering therapies have failed to produce any tangible benefit; neither diminishing disease prevalence nor progression [6,7].…”
Section: Introductionmentioning
confidence: 99%